MASALAH DAN DINAMIKA IMPLEMENTASI KEBIJAKAN PUBLIK TENTANG TRANSPORTASI (Kajian Di Kota Tasikmalaya, Jawa Barat) - Asmawi, Awing; Sjoraida, Diah Fatma; Anwar, Rully Khairul (CosmoGov, 2017)
This article discusses how public policy on transport can have the issues and the dynamics of its implementation in society. The study was conducted in Tasikmalaya City, West Java, Indonesia. It is important to the society because the development of transport services has a very close relationship with social welfare and economic growth of a region. It can be shown with an indication that the region has a complete transportation system that works better than the other regions, then these regions tend to have a better level of social welfare and economic growth. Conversely, the presence of transport less functioning properly will result in the emergence of social and environmental problems. The study used a multiple case study method. The cases consist of activities in the implementation of Tasikmalaya city government outreach programs to the community regarding transport. Interviews, observation and document analyses were used to collect the data. Face-to-face interviews using a list of questions had been developed for this study. The findings of the study indicate that in addition to designing their own and carry out the development plans of transport in Tasikmalaya City itself, there are also the plans involving the West Java provincial government, and even national government of Indonesia.